Fandom dan interaksi parasosial dalam TikTok - Prameswari, Andyra; Tanjung, Sumekar (Jurnal Mahasiswa Komunikasi Cantrik, 2025)
TikTok is used by K-Pop fans in Indonesia to get the latest information about their idols. Fans even produce K-Pop content to show their favorite groups to other TikTok users. This study aims to describe the parasocial interactions carried out by K-Pop fans from four different fandoms while using TikTok as their main social media. This qualitative study applied purposive sampling and in-depth interview techniques. The findings stated that although the four informants came from different K-Pop fandoms, their processes in carrying out parasocial interactions on TikTok were quite similar, despite having different experiences. In the cognitive response classification, the highest level of parasocial interaction experienced by the four informants was the construction of persona and self relations. In the affective response, it was the empathy/counter empathy process, and in the behavioral response, through non-verbal behavior.